PENERAPAN TEKNOLOGI WEB DALAM SISTEM PEMESANAN MAKANAN: SYSTEMATIC LITERATURE REVIEW 2020–2025 - Muh Ridwan; Ashar Ashar; Dimas Reskianto; Reza Alfiansa; Dhimas Tribuana; Dayanti Dayanti (Plexi Digital Indonesia, 2026)
The development of web technologies has brought significant changes to modern food ordering systems. This SLR addresses the gap in synthesizing web technology trends for Food Ordering Systems (FOS) from 2020–2025 by reviewing 30 articles from Google Scholar, ScienceDirect, and IEEE Xplore.of web technologies in Food Ordering Systems during the years 2020–2025. This study reviews 30 articles from various databases such as Google Scholar, ScienceDirect, and IEEE Xplore. Analysis reveals dominant technologies: Laravel (35%), React (25%), MySQL (65%), alongside payment APIs, Firebase real-time databases, with growing focus on security (HTTPS/JWT) and UX, payment API integration, the use of real-time databases such as Firebase, and increasing attention to security and user experience aspects. Findings highlight implementation challenges (security, scalability) and recommend cloud-based, secure frameworks for future FOS development.